A Simplified Technique for Arthroscopic Reduction and Double-Pulley Fixation of Bony Bankart Lesion by Percutaneous Spinal Needle Suture - Fashuai Wu, M.D., Ph.D.; Wenbo Yang, M.D., Ph.D.; Chunqing Meng, M.D., Ph.D.; Hong Wang, M.D., Ph.D.; Wei Huang, M.D., Ph.D. (Arthroscopy Techniques)
Bony Bankart lesion is commonly seen and highly associated with anterior glenohumeral instability. However, the reported arthroscopic techniques that reduce and fix bony Bankart lesion with traditional suture devices may encounter several problems during the suture-passing process, including splitting the fracture fragment or surrounding soft tissue, resulting in iatrogenic damage, and causing difficulties for instrument operation and suture management. Here, we have proposed a simplified technique for arthroscopic reduction and fixation of bony Bankart lesion by the introduction of percutaneous suturing with a spinal needle, which has a lower risk of iatrogenic damage, lower possibility of splitting the fracture fragment or surrounding soft tissue, and less difficulty in suturing during operation and suture management. Our technique, a combination of percutaneous spinal needle suture passing and s double-pulley suture-tying technique, is less invasive to patients, more convenient and economical, and more suitable for beginners, which is challenging to achieve with a traditional suture device. In addition, the equipment used in our technique is commonly seen and accessible in the operating room, without requiring high-value consumables and supporting instruments. In summary, our technique, integrating economy, simplicity, reliability, and safety, has very good application potential in clinical situations.